PTU-124 An External Validation Of The Hepatoma Arterial-embolisation Prognosis (hap) Score: The Liverpool Experience. (9th June 2014) - Noorullah, O; Lekharaju, VP; Din, IU; Klcova, J; Cross, T; Evans, J; Sturgess, R; Palmer, D; O'Grady, E; Stern, N
Abstract : Introduction: Most Hepatocellular Carcinomas (HCCs) have palliative treatment. Trans-arterial embolisation (TAE) or chemoembolisation (TACE) are used with variable results. The HAP score was recently described to determine patients likely to benefit from TAE or TACE. We report our experience with TAE and TACE to assess whether the HAP score was valid for our cohort of patients. Methods: Retrospective review of cases given TAE or TACE in Liverpool, UK (2006–2013). HAP score [1 point each for albumin < 36 g/dl, AFP > 400 ng/ml, Bilirubin > 17 µmol/l, tumour diameter > 7cm. HAP A = 0 points, B = 1, C = 2, D >2]. Outcome recorded according to HAP score. Results: 137 patients identified having received TAE/TACE with full data to complete HAP score. Mean age 69; 116 (84.7%) male. 78.8% AUH, 21.2% RLUH. HAP score A: 44 (32.1%); B: 40 (29.2%); C: 32 (23.4%); D: 21 (15.3%). Overall median survival 492 days (16 months). Median survival by HAP score, A: 492 days; B: 839 days; C 478 days; D 309 days. Log rank p < 0.001. Survival at 1 year: A 62.8%; B 75%; C59.4%, D 28.6%. Survival at 2 years: A 29.5%, B 52.5%, C 37.5%, D 14.3%. HAP D patients had lower median survival (309 vs. 563 days; p < 0.001) and 1 and 2 year survival (28.6 vs. 65.5%; p = 0.001 and 14.3 vs 39.7%; p = 0.021). Conclusion: Patients with HAP score D due TACE have a relatively poor outcome in this external validation group. This should be considered when planning treatment or further trials. Reference: Kadalayil et al . Annals of Oncology 2013 Disclosure of Interest: None Declared.